The Religious Condition of Poland’s High School Youth in the Years 1988-2017 - Janusz Mariański (Paedagogia Christiana, 2020)
Poland’s youth are changing in a dynamic way, in short intervals, in various ways and in different social environments. This article presents the selected results of sociological research undertaken four times over the years 1988-2017 on nationwide samples of Poland’s youth attending secondary schools. It was conducted using a distributed questionnaire, meaning that we provided questionnaires to students who were present on a given day in classes at school. Youth religiosity was diagnosed according to several basic parameters: confessional and religious self-identification, young people’s attitudes towards the dogmas of the faith, and religious practices, both in static and dynamic cross-sections. The current status of the religiousity of secondary school youth and its transformation in 1988-2017 indicates accelerated processes of secularisation in Polish society. The thesis about the accelerated “secularisation creeping in” is becoming increasingly more legitimate.